A study to find the various causes for compressive myelopathy - Krishna Mohan, Pottala; Sudha, K Jaya; Anvitha, M; Chandra, T. Jaya (International Journal of Medical Research and Review, 2020)
Introduction: Myelopathy was the term that describes any neurologic defect related to the spinal cord. A study was conducted to evaluate various causes of compressive myelopathy and also MR characterization of spinal cord compressive lesions. Materials and Methods: It is a hospital-based cross-sectional study, conducted in the department of radiodiagnosis, GSL Medical College, Rajahmundry from December 2014 to August 2016. All patients referred to the department of radiology with symptoms of compressive myelopathy of the spine were included. Pre-contrast scanning was done using TiWI, T2WI, FLAIR Sagittal, STIR sagittal. A Chi-square test was used to find the statistical significance, P > 0.05 was considered to be statistically significant. Results: During the study period total of 30 participants were included, spinal TB was diagnosed to be the most common cause of myelopathy (13; 43.3%) Extradural myelopathy was diagnosed in 23 (76.6%) participants and intradural in 7 (23.3%) members. Statistically, there was no significant difference between the age and cause for myelopathy and also between the gender. Conclusion: The most common cause of compressive myelopathy was identified to be extradural compression form TB followed by trauma. Spinal TB was the commonest site involved. In spine injury, the common site involved was the thoracic.